2007
DOI: 10.1002/jbm.b.31009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo response of porous hydroxyapatite and β‐tricalcium phosphate prepared by aqueous solution combustion method and comparison with bioglass scaffolds

Abstract: Pure hydroxyapatite (HAp) and a biphasic calcium phosphate [containing 90% of beta-tri-calcium phosphate (beta-TCP) and 10% HAp] were tailored through an aqueous solution combustion synthesis. Porous struts were prepared using all the powders along with bioglass, a known bioactive material, and subsequently characterized. Sterilized struts were implanted to the lateral side of radius bone of 24 black Bengal goats of either sex, in which a blank hole was left unfilled in a group of six specimens to act as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(97 citation statements)
references
References 37 publications
2
93
0
2
Order By: Relevance
“…In vivo results have confirmed that BG is able to stimulate and promote neo-vascularization [52,55,[120][121][122]164,203,206,[208][209][210][211]. For example, Leu et al [211] filled calvarial defects in SpragueDawley rats with 45S5 Bioglass ® impregnated (1.2 mg) collagen sponges (volume = 0.05 cm 3 ) and unloaded, empty sponge as a control.…”
Section: Effect Of Bioactive Glass On Angiogenesismentioning
confidence: 91%
See 3 more Smart Citations
“…In vivo results have confirmed that BG is able to stimulate and promote neo-vascularization [52,55,[120][121][122]164,203,206,[208][209][210][211]. For example, Leu et al [211] filled calvarial defects in SpragueDawley rats with 45S5 Bioglass ® impregnated (1.2 mg) collagen sponges (volume = 0.05 cm 3 ) and unloaded, empty sponge as a control.…”
Section: Effect Of Bioactive Glass On Angiogenesismentioning
confidence: 91%
“…Bioactive silicate glasses exhibit several advantages in comparison to other bioactive ceramics, e.g., sintered hydroxyapatite, in tissue engineering applications. For example, it has been demonstrated that dissolution products from bioactive glasses up-regulate the expression of genes that control osteogenesis [7,51], which explains the higher rate of bone formation in comparison to other inorganic ceramics such as hydroxyapatite [52]. Further studies using 45S5 Bioglass ® particles have shown encouraging results regarding potential angiogenic effects of Bioglass ® , i.e., increased secretion of vascular endothelial growth factor (VEGF) and VEGF gene expression in vitro, as well as enhancement of vascularization in vivo [53][54][55][56] (see §4).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vivo studies using different animal models described an effect of 45S5 Bioglass Ò on the angiogenic response in soft connective and bone tissue. 16 Ghosh et al 19 and Nandi et al…”
mentioning
confidence: 99%